ДОСЛІДЖЕННЯ ВТРАТ ТА ОБЕРТАЛЬНОГО МОМЕНТУ БЕЗПАЗОВОГО МАГНІТОЕЛЕКТРИЧНОГО ДВИГУНА З МАСИВНИМ ОСЕРДЯМ СТАТОРА - Петухов, І.С.; Кіреєв, В.Г.; Акінін, К.П.; Ісаєв, Є.В. (Інститут електродинаміки НАН України, Київ, 2025)
The efficiency of the structure and the low cost of preparation of production of non-steady electric motors with permanent magnets and massive stator core. The design of the experimental installation for measuring losses in a solid stator core will be laid out. The stages of the method of calculating these losses are formulated. To calculate the losses from eddy currents used the software complex "Comsol multiphysics". The hysteresis losses were calculated by the Steinmetz formula. For different density of the calculated grid, the loss of losses in the massive core was made and a comparison was made with the results of measurements in the rotation speed range 0… 3600 rpm. To calculate the maximum moment in statics, a model of winding with a sinusoidal spatial form of MRS was used. The dependences of the rotational moment on the speed of rotation in the study range was computed. Sufficient accuracy of the calculation methodology is noted. References 12, figures 8, tables 1.